2018
DOI: 10.3390/ijerph15050927
|View full text |Cite
|
Sign up to set email alerts
|

In Hospital Stroke Mortality: Rates and Determinants in Southwestern Saudi Arabia

Abstract: Objectives: The present study analyzed in-hospital first-time stroke mortality in southwestern Saudi Arabia over one-year to assess the in-hospital stroke case fatality rate, mortality rate and explore the factors associated with in-hospital stroke mortality. Study Design: Hospital based follow-up study. Methods: First-time stroke patients admitted to all hospitals in Asser region over one-year period (January through December 2016) were included in the study. Data about personal characteristics, pre-stroke hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
25
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 29 publications
13
25
4
2
Order By: Relevance
“…In agreement with our study, a study conducted in South London 2 found that pre-stroke hypertension was not an independent predictor of patient survival and hypertensive patients had a 1% lower hazard of death as compared to non-hypertensive adult stroke patients. These findings were in contradiction with the study done in Saudi Arabia, 1 whereby hypertensive patients had a 77% higher hazard of death as compared to non-hypertensive adult stroke patients. This might be due to differences in sample size, follow up period, and the proportion of hypertensive and non-hypertensive patients.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In agreement with our study, a study conducted in South London 2 found that pre-stroke hypertension was not an independent predictor of patient survival and hypertensive patients had a 1% lower hazard of death as compared to non-hypertensive adult stroke patients. These findings were in contradiction with the study done in Saudi Arabia, 1 whereby hypertensive patients had a 77% higher hazard of death as compared to non-hypertensive adult stroke patients. This might be due to differences in sample size, follow up period, and the proportion of hypertensive and non-hypertensive patients.…”
Section: Discussioncontrasting
confidence: 98%
“…24 In our study, admission GCS score was the independent predictor of patient survival, patients who had a GCS score of 3-8 had ten times higher hazard of death as compared to those having a GCS score of 13-15. This was in line with the study done in Saudi Arabia, 1 where an altered level of consciousness at presentation had a significantly higher hazard of intra-hospital mortality. Similarly, a study conducted in south London, 2 found two times the higher hazard of death among patients who had moderate to severe brain injury as compared to alert patients.…”
Section: Discussionsupporting
confidence: 91%
“…Grube and colleagues reported that persons aged ≥85 years were more likely to die after stroke compared with those aged <65 years (odds ratio [OR]; 13.50, 95% CI; 5.54–32.89) [ 26 ]. In our study, almost one in five (18.2%) of the cohort experienced in-hospital death, which was higher compared to that reported among cohorts of older adults in Italy (10.9%) [ 14 ], China (3.1%) [ 30 ], Saudi Arabia (11.0%) [ 31 ], and Canada (13.4%) [ 32 ], although a recent study reported a much higher (35.7%) in-hospital stroke death rate in Turkey [ 33 ]. The differences were likely to be due to a myriad of factors, including study design, disease definition, local factors (e.g., the standard of hospital care or treatment received), but particularly due to the fact that, in the other studies, all patients had ischaemic stroke, for which the case fatality was significantly lower than for haemorrhagic stroke [ 34 ].…”
Section: Discussioncontrasting
confidence: 71%
“…The reasons for these sexual difference may include decreased understanding of stroke in women [10], increase in incidence and poor management of risk factors [5,11], delays in admission to hospital [12], altered symptomatology leading to missing the diagnosis or delay in diagnosis [12,13], fewer investigations during the acute admission [13], less specialized care following admission [14], higher frequency of complications, and biological difference in endothelial and other functions in the 2 sexes [15]. Although a few studies from the Middle East have reported on the sexual differences in the risk factor profile [16], clinical presentation, and outcome of stroke [17], to our knowledge, there is no study reporting specifically on the effect of sexual difference in major adverse cardiovascular events (MACEs). We have previously reported on the risk factors, clinical presentation, and outcome following AS in a diverse group of patients in Qatar [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%